5 - Les nouvelles formes de mobilisation et leur apport dans la décentralisation en République du Congo : analyse à partir de l’expérience de Pointe-Noire, à l’aune des « nouveaux Nouveaux Mondes » de Georges Balandier - Osséré NGANONGO (African Sociological Review, 2021)
[En]The control of political spaces by some regimes prevents the mobilization of opposition in such spaces. This has led to the emergence of new forms of mobilization through social networks, which encourage the emergence of new forms of engagement, of participation in debates and the emergence of a new type of political actor in these virtual worlds called “new New Worlds” by Georges Balandier. In these spaces interactions between actors allow the appropriation of devolution processes by making citizens committed actors, attached to their territory, and, involved in ongoing dynamics.